IOC Manual of sports cardiology (Wiley-Blackwell, 2017)
The sudden death of an athlete is a highly tragic and emotional event. Recent data suggest that death rates are greater than previously reported and a screening strategy with the 12-lead electrocardiogram (ECG) may help identify those athletes at risk. One of the main concerns about cardiac testing in athletes is the high number of false positive rates because athletic conditioning is associated with a number of electrical and structural modifications which occasionally overlap with disorders commonly implicated in sudden cardiac death.